The Effectiveness of Mycorrhizal and Nitrogen Fertilizer on the Production of Chili (Capsicum annuum) in Tidal Land - Widya Irmawati; Nuni Gofar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Irmawati W, Gofar N. 2020. The effectiveness of mycorrhizal and nitrogen fertilizer on the production of chili (Capsicum annum) in tidal land. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 175-183.Mycorrhizal fertilizer and urea can be used as an alternative to overcome problems in the tidal land that have various obstacles including low availability of nutrients, the presence of toxic compounds, high salinity, and pyrite compounds to be developed as agricultural land. The purpose of this research was to determine the role of mycorrhizal fertilizer and urea on the yield of chilli (Capsicum annuum) in tidal land. The study used a Randomized Block Design Method with 4 treatments including control, Mychorrhizal 10 g, Mychorrhizal 10 g and urea 0,375 g, urea 0,375 g with 5 replicat. So that the total treatments are 20 units. The results show that the application of mycorrhizal fertilizer 10 g had affected on plant height, number of leaves, and leaf area. Plants that have mycorrhizae have the ability to absorb more macro and micronutrient. The presence of fungal hyphae can expand the area of absorption of nutrients and water so that plant nutrients are available. The low treatment of mycorrhizal and urea fertilizers was due to a decrease in fertilizer efficiency because fertilizer was given in excessive amounts.